STRATEGI PEMBELAJARAN AKTIF TERHADAP KEMAMPUAN PSIKOMOTORIK SISWA PADA MATA PELAJARAN FIQH - Abdullah Ali (AZKIA : Jurnal Aktualisasi Pendidikan Islam, 2022)
The title of this research is "Active Learning Strategy on Students' Psychomotor Ability in Fiqh Subjects". The purpose of this study was to determine the effect of active learning strategies on students' psychomotor abilities. In this study the author uses a descriptive method. Data collection techniques through observation, interviews, and questionnaires. Based on the results of the study, it can be concluded that the psychomotor abilities of students increased after the use of active learning strategies in Fiqh subjects. This can be seen from the steps, and the use of interesting media in helping to implement active learning strategies. The supporting and inhibiting factors in realizing this are teacher guidance and control, the use of interesting media, and the use of various learning strategies. Teachers are good at implementing active learning strategies and have a positive effect.